Current ankle sprain prevention and management strategies of netball athletes: a scoping review of the literature and comparison with best-practice recommendations - Patrick L. Rowe; Adam L. Bryant; Kade L. Paterson (BMC, 2021)
Abstract Background Ankle sprains are the most commonly reported injury in netball. Approximately four in five netball athletes will sustain an ankle sprain, up to half will go on to sustain recurrent ankle sprains, and nine in ten report perceived ankle instability. Historically, prevention and management strategies of ankle sprains and injuries have been investigated for a variety of sports, however, no literature reviews have investigated these in netball athletes, or compared these with current best-practice within the literature. Therefore, this scoping review aims to understand how netball athletes currently prevent and manage ankle sprains and to compare these approaches with best-practice recommendations. Methods A literature search was conducted using MEDLINE, CINAHL, and SPORTDiscus databases using keywords to capture studies with data or information related to the prevention and management of ankle sprains and injuries in netball. Results The search strategy captured 982 studies across all databases, with 30 netball studies included in this scoping review. Studies suggest netball athletes are not commonly referred to health professionals, do not undertake adequate rehabilitation, and almost immediately return to court following an ankle sprain or injury. Current best-practices suggest injury prevention programs and external ankle support effectively reduce ankle sprains and injuries; however, poor compliance and implementation may be a significant barrier. Currently, there is a lack of evidence that netball-specific footwear reduces the risk of ankle sprains. Conclusion The findings suggest netball athletes do not implement current best-practice prevention and management strategies following an ankle sprain. This is despite evidence of the effectiveness of injury prevention programs, external ankle support, and adequate rehabilitation in reducing ankle sprain rates. Current-best practice prevention and management of ankle sprains should be considered by clinicians, coaches, and athletes to reduce the prevalence and chronicity of ankle sprains in netball.